2015
DOI: 10.1001/jamaoto.2014.3399
|View full text |Cite
|
Sign up to set email alerts
|

Association of Decreased Rate of Influenza Vaccination With Increased Subjective Olfactory Dysfunction

Abstract: Influenza vaccination seems to be associated with a decreased rate of subjective olfactory dysfunction. This is a preliminary finding, and further studies would be needed to elucidate the exact role of influenza and influenza vaccination in patients with olfactory loss.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(15 citation statements)
references
References 19 publications
3
12
0
Order By: Relevance
“…They suggested that other mechanisms, apart from nasal obstruction, can be responsible for olfactory loss in this setting [31]. The exact [9,32]. There was no significant relationship between sinonasal symptoms and olfactory loss in our study, which may support this proposed mechanism.…”
Section: Discussionsupporting
confidence: 56%
See 3 more Smart Citations
“…They suggested that other mechanisms, apart from nasal obstruction, can be responsible for olfactory loss in this setting [31]. The exact [9,32]. There was no significant relationship between sinonasal symptoms and olfactory loss in our study, which may support this proposed mechanism.…”
Section: Discussionsupporting
confidence: 56%
“…There was no relation between the upper respiratory tract involvement and olfactory loss in our patients. This may suggest that the olfactory loss is not due to generalized mucosal edema and nasal obstruction, which occurs during a common upper respiratory infection [9].…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…In the 2018-2019 influenza season, 34,200 deaths were recorded in the USA by the Center for Disease Control and Prevention (https://www.cdc.gov/flu/about/burden/ 2018-2019.html). Vaccination against Influenza was shown to negatively correlate with the incidence of smell loss, however this study needs confirmation with a larger cohort number (68).…”
Section: Anosmia Caused By Influenza or Common Coldmentioning
confidence: 64%